BUKTI KEBENARAN AL-QURAN - Sri Aliyah (JIA (Jurnal Ilmu Agama), 2015)
Al Quran is the greatest miracles of Muhammad SAW as the direction of humankind in order to reach eternal happiness. Scientific evidences show that Al Quran has the truth massages, although it was released far before the finding of modern sciences. The researches continue to study the truth of Al Quran an it revealed the historical fact.